GW24-e2125 PROTECTIVE EFFECTS OF A PRESCRIPTION OF JIASHEN ON MYOCARDIAL INFARCTION VIA INHIBITION OF INFLAMMATION IN RATS. (1st October 2013) - Xie, Shiyang; Wang, Youping; Li, Bin; Nan, Xiaoli; Liu, Yanyan; Zhang, Boli; Zhu, Mingjun
Abstract : Objectives: To determine the role of inflammation in myocardial protection induced by a prescription of Jiashen (PJS) in the early period of myocardial infarction (MI) in rats. Methods: MI was induced by the ligation of left anterior descending coronary artery in Sprague-Dawley rats. The rats were divided into five groups: sham-operated group; MI + vehicle group; PJS-3g (3 g/kg/day) group; PJS-6g (6g/kg/day) group and losartan (10 mg/kg/day) group. Infarct size (IS) was determined by Evans blue and 2, 3, 5-Triphenyltetrazolium chloride (TTC) 3 days after MI; the left ventricular structure and function were measured by echocardiography performed 1 week after MI; and myocardial inflammatory mediators including tumour necrosis factor-α (TNF-α), interleukin-1β (IL-1β), monocyte chemoattractant protein-1 (MCP-1) were measured by ELISA. Results: Compared with the MI + vehicle group, treatment with PJS at the dose of 6 g/kg/day reduced myocardial IS ( P < 0.05), left ventricular end diastolic diameter (LVEDD) and left ventricular end systolic diameter (LVESD) ( P < 0.01), and enhanced left ventricular ejection fraction (LVEF) and left ventricular fractional shortening (LVFS) ( P < 0.01). Compared with the MI + vehicle group, administration of PJS dose-dependently attenuated the increased levels of TNF-α, IL-1β and MCP-1 in ischaemic myocardium ( P < 0.01). PJS at the dose of 6 g/kg/day had equally effectiveness with losartan. Conclusions: Our studies showed that consistent with losartan-induced cardioprotection, PJS administered after MI reduced myocaidial IS and improved cardiac function that was associated with the decreased inflammatory mediators. The data indicate that PJS exert its cardioprotection possibly via inhibiting inflammatory response.